Extended UTAUT Model of E-Government Adoption Intention Among Civil Servants in Cambodia - Vandara Mov; Samnang Ann; Sothearith Try (Srawung: Journal of Social Sciences and Humanities, 2026)
This study examined the factors influencing government personnel's behavioral intention to adopt and use e-government services across three institutions in Cambodia. A quantitative approach was adopted, employing a multi-stage sampling technique that combined stratified random sampling with purposive sampling. Data were collected from 500 government officials across three Cambodian ministries who had prior experience using e-government services. Structural equation modeling (SEM) and confirmatory factor analysis (CFA) were used to test the validity, reliability, and hypothesized relationships among the study constructs. The results showed that social influence, accessibility, facilitating conditions, performance expectancy, trust in government, and trust in the internet all significantly predicted behavioral intention, with social influence exerting by far the strongest effect, followed by accessibility, facilitating conditions, performance expectancy, trust in government, and trust in the internet. Effort expectancy, by contrast, did not significantly predict behavioral intention. Behavioral intention, in turn, significantly predicted actual user behavior. These findings extend the Unified Theory of Acceptance and Use of Technology by demonstrating that, among government personnel, social and institutional factors carry greater explanatory weight than perceived ease of use, a pattern that departs from findings typically reported for citizen populations. The results offer practical guidance for government agencies seeking to strengthen e-government adoption, particularly through measures that build institutional trust, improve service accessibility, and mobilize social endorsement among users.